Ultrasonically-assisted surface modified TiO2/rGO/CeO2 heterojunction photocatalysts for conversion of CO2 to methanol and ethanol - Panpailin Seeharaj; Panyata Kongmun; Piyalak Paiplod; Saowanee Prakobmit; Chaval Sriwong; Pattaraporn Kim-Lohsoontorn; Naratip Vittayakorn (My University, 2019)
Converting CO2 to usable fuel may contribute to lowering of global warming, thus this study developed effective heterojunction photocatalysts for the photoreduction of CO2 with water into methanol and ethanol fuels. The photocatalysts were prepared from combining surface modified titanium dioxide (TiO2) nanoparticles with reduced graphene oxide (rGO) and cerium oxide (CeO2). The TiO2 surfaces were firstly modified via the sono-assisted exfoliation, with high intensity ultrasonic waves (ultrasonic horn, 20 kHz, 150 W/cm2) in 10 M NaOH for 1 h. Highly reactive nanosheets delaminated from outer surfaces of the primary TiO2 crystals leading to an increase in specific surface active area, light absorption and decrease in electron-hole recombination rate, which enhanced photocatalytic activity. Then, 0.75 wt% rGO and 1 wt% CeO2 were incorporated into the surface modified TiO2 to promote photogenerated charge separation, electron mobility and CO2 absorptivity. The modified TiO2/rGO/CeO2 photocatalysts exhibited superior photocatalytic performance by producing methanol at 641 μmol/gcath and ethanol at 271 μmol/gcath, almost 7 times higher than rates from pure TiO2. The significant improvement in CO2 photoconversion activity was mainly attributed to the high interfacial contact area and strong connection between the reactive delaminated TiO2 nanosheets, rGO and CeO2, which, in turn, facilitated the flow of large number of photogenerated charge carriers to react with the absorbed species, and the multi-step charge transportation due to the heterojunction effect that effectively retarded electron-hole recombination.
Keywords: Titanium Dioxide; Exfoliation joint; Specific surface area; Charge carrier; Advanced Photocatalysis Techniques